Accidental traffickers: qualitative findings on labour recruitment in Ethiopia - Joanna Busza; Zewdneh Shewamene; Cathy Zimmerman; Annabel Erulkar; Eyasu Hailu; Lemi Negeri; Elizabeth Anderson; Yuki Lo (BMC, 2023)
Abstract Background The growth of labour migration and associated risks of human trafficking and exploitation remain significant global human rights and health challenges. There is increasing policy interest in addressing structural determinants of adverse migration outcomes such as migrants' use of informal employment recruiters. In Ethiopia, "safe migration" policies have introduced regulations for registered private employment agencies and penalties for anyone else placing migrants into work overseas. Yet migrants continue to use informal facilitators who are often demonised as traffickers without evidence of their motivations, experiences or perceptions. We conducted qualitative interviews with 28 informal facilitators as part of a study into how recruitment practices shape risks for female migrants seeking domestic work in the Middle East and Gulf States. We present the realities of irregular recruitment on the ground, and how these practices are affected by policies that dichotomise recruiters into legal/safe and illegal/unsafe categories. Results We identified four main themes. First, arranging migration from rural areas differs from in the capital, Addis Ababa, where laws and regulations originate. Outside Addis Ababa, registration was difficult for facilitators to arrange, with little incentive to do so due to its lack of importance to prospective migrants. Second, the ability to circumvent legal requirements was considered an advantage of informal facilitators because it reduced costs and expedited migrants' departure. Third, facilitators did not work alone but operated in long "chains" of diverse actors. This meant migrants' safety was not determined by any given individual, but spread across numerous people involved in sending a migrant abroad, some of whom might be registered and others not. And finally, facilitators did not believe they could realistically safeguard migrants once they were outside of Ethiopia and working under different laws and employers. Conclusions Findings from this study add to a growing body of work demonstrating the diversity of people involved in the migration process, and consequent oversimplification of popular policy solutions. A more effective approach might be to constructively engage informal facilitators and identify ways they could assist with referring migrant workers to registered agencies and safe employment, rather than criminalising their participation.